2018
DOI: 10.1093/neuros/nyy076
|View full text |Cite
|
Sign up to set email alerts
|

Flow Diversion of Posterior Circulation Cerebral Aneurysms: A Single-Institution Series of 59 Cases

Abstract: This is a large single-institution series of Pipeline (Medtronic Inc) for posterior circulation aneurysms and demonstrates acceptable safety and effectiveness in these challenging cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 28 publications
5
41
0
Order By: Relevance
“…With published reports of safe off label use for aneurysms beyond the petrous to ophthalmic ICA and development of second generation FDS, the IFU has since expanded to small (<7 mm) and medium (7-15 mm), wide neck aneurysms of the entire intracranial ICA. To date, safe off-label use has been reported for cerebral aneurysms in most cerebrovascular territories with a parent vessel diameter of 2-5 mm 6,9,10,16,18,21,26,47,73,94,107,120,121) .…”
Section: Development Of Flow-diverting Stents (Fds)mentioning
confidence: 99%
See 3 more Smart Citations
“…With published reports of safe off label use for aneurysms beyond the petrous to ophthalmic ICA and development of second generation FDS, the IFU has since expanded to small (<7 mm) and medium (7-15 mm), wide neck aneurysms of the entire intracranial ICA. To date, safe off-label use has been reported for cerebral aneurysms in most cerebrovascular territories with a parent vessel diameter of 2-5 mm 6,9,10,16,18,21,26,47,73,94,107,120,121) .…”
Section: Development Of Flow-diverting Stents (Fds)mentioning
confidence: 99%
“…Mortality rates were lower in the reconstructive group (4.0% vs. 10.0%) but the difference was not statistically significant. In a single center series of 59 cases, Bender et al 6) achieved 78% complete occlusion using FDS for posterior circulation aneurysms with a 9% complication rate. These results were somewhat at odds with contemporary case series, but the authors attributed their improved results to a preponderance of posterior circulation aneurysms isolated to the vertebral artery in their series 6) .…”
Section: Non-saccular and Posterior Circulation Aneurysmsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ow diversion in vertebral and basilar artery aneurysms carries a high risk of periprocedural stroke, and might be associated with high overall mortality. [14][15][16] Numerous studies showed that LVIS stents also have ow diverting effects to minimize aneurysmal hemodynamics. [7,17] Wang et al [7] quanti ed the ow diverting effects of the LVIS device, and compared the effect with the Pipeline device (Chestnut Medical Technologies, Menlo Park, CA) and the Enterprise stent.…”
Section: Angiographic Results At Follow-upmentioning
confidence: 99%